Wearable Piezoelectric Yarns with Inner Electrodes for Energy Harvesting and Signal Sensing (Adv. Mater. Technol. 6/2022). Issue 6 (7th June 2022) - Ryu, Chul Hee; Cho, Jae Yong; Jeong, Se Yeong; Eom, Wonsik; Shin, Hwansoo; Hwang, Wonsoep; Jhun, Jeong Pil; Hong, Seong Do; Kim, Taeyun; Jeong, In Wha; Sung, Tae Hyun
Abstract : Piezoelectric Yarns In article number 2101138, Tae Hyun Sung and co‐workers present an inner‐electrode piezoelectric yarn (IEPY) that shows excellent durability, flexibility, and high signal accuracy through noise minimization which are required performance characteristics of the wearable sensor devices. The IEPY used during the process has excellent tensile strength and strong durability, maintaining its performance over 105 cycles under pushing force of 60 kg and generating excellent piezoelectric output energy.